2011
DOI: 10.1037/a0023763
|View full text |Cite
|
Sign up to set email alerts
|

Amphetamine-induced incentive sensitization of sign-tracking behavior in adolescent and adult female rats.

Abstract: Age-specific behavioral and neural characteristics may predispose adolescents to initiate and escalate use of alcohol and drugs. Adolescents may avidly seek novel experiences, including drugs of abuse, because of enhanced incentive motivation for drugs and natural rewards, perhaps especially when that incentive motivation is sensitized by prior drug exposure. Using a Pavlovian conditioned approach (PCA) procedure, sign-tracking (ST) and goal-tracking (GT) behavior was examined in amphetamine-sensitized and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
37
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(48 citation statements)
references
References 39 publications
10
37
1
Order By: Relevance
“…Given that bLRs and bHRs are known to differ in these behaviors, the effects of adolescent cocaine treatment on Pavlovian conditioned approach behavior were analyzed separately within each phenotype. Contrary to what we initially hypothesized based, in part, on previous findings (Doremus-Fitzwater and Spear 2011; McClory and Spear 2014; Saddoris et al 2016), bLR rats exposed to cocaine during adolescence did not acquire a sign-tracking response as measured by the number of lever-CS contacts, probability to approach the lever-CS, and latency to contact the lever-CS (Fig. 4 a–c).…”
Section: Resultscontrasting
confidence: 96%
See 2 more Smart Citations
“…Given that bLRs and bHRs are known to differ in these behaviors, the effects of adolescent cocaine treatment on Pavlovian conditioned approach behavior were analyzed separately within each phenotype. Contrary to what we initially hypothesized based, in part, on previous findings (Doremus-Fitzwater and Spear 2011; McClory and Spear 2014; Saddoris et al 2016), bLR rats exposed to cocaine during adolescence did not acquire a sign-tracking response as measured by the number of lever-CS contacts, probability to approach the lever-CS, and latency to contact the lever-CS (Fig. 4 a–c).…”
Section: Resultscontrasting
confidence: 96%
“…Others have previously shown that exposure to drugs of abuse (i.e., amphetamine, ethanol) in adolescence enhances the tendency to sign-track in outbred rats (Doremus-Fitzwater and Spear 2011; McClory and Spear 2014), and similar increases in sign-tracking behavior were reported in adult rats after cocaine self-administration (Saddoris et al 2016). The seemingly discrepant results reported here are likely due to the use of selectively-bred bLR rats, which, unlike outbred rats, have an inherent predisposition towards goal-tracking behavior (Flagel et al 2010), amongst other inborn traits (Flagel et al 2014).…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…A second potential limitation to the interpretation of the current results is the extent to which the findings are selective to alcohol exposure in adolescence. Previous studies have investigated the effect of nicotine and amphetamine exposure during adolescence on Pavlovian conditioned approach behavior in adulthood (Quick et al, 2014;Doremus-Fitzwater and Spear, 2011). Adolescent nicotine exposure (on PND 31-45) was shown to increase approach to a CS in male animals, whereas approaches to the CS were reduced in females.…”
Section: Discussionmentioning
confidence: 99%
“…Emergence of ST is thought to reflect the motivational property of the reward, and has the potential to develop into “pathological” incentive salience (Flagel, Akil, & Robinson, 2009; Robinson & Berridge, 2003). Sign tracking has also been linked to addiction-like behaviors (Tomie, Grimes, & Pohorecky, 2008) and can be induced by drugs of abuse (Doremus-Fitzwater & Spear, 2011; Uslaner, Acerbo, Jones, & Robinson, 2006). Our lab has previously shown that sign tracking in the PCA task seen in adulthood is sensitive to adolescent stress exposure (Anderson & Spear, 2011).…”
Section: Introductionmentioning
confidence: 99%